1992
DOI: 10.1042/cs0830375
|View full text |Cite
|
Sign up to set email alerts
|

Nyctohemeral changes in bone turnover assessed by serum bone Gla-protein concentration and urinary deoxypyridinoline excretion: effects of growth and ageing

Abstract: 1. To investigate whether there is a nyctohemeral rhythm in bone turnover, we measured serum bone Gla-protein (osteocalcin, an index of osteoblast activity) concentration every 2h and urinary deoxypyridinoline (a marker of bone collagen resorption) excretion for 8h periods in 10 pubertal girls (aged 10-14 years), 15 premenopausal women (aged 20-49 years) and 17 postmenopausal women (aged 50-75 years). 2. The serum concentration of bone Gla-protein and the urinary excretion of deoxypyridinoline were five times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 14 publications
(17 reference statements)
8
36
0
Order By: Relevance
“…Indeed, OC, PICP, and ICTP levels follow a similar circadian rhythm with peak values occurring in early morning and nadirs in the afternoon (1,30,37). Circadian variation in bone markers appears to be unaffected by age and sex (38), as well as by growth and ageing (39). Furthermore, in children with GHD, we previously demonstrated that both nocturnal and diurnal 12-h mean data for OC and PICP were significantly lower than controls, but the pattern of their circadian rhythms was maintained (30).…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, OC, PICP, and ICTP levels follow a similar circadian rhythm with peak values occurring in early morning and nadirs in the afternoon (1,30,37). Circadian variation in bone markers appears to be unaffected by age and sex (38), as well as by growth and ageing (39). Furthermore, in children with GHD, we previously demonstrated that both nocturnal and diurnal 12-h mean data for OC and PICP were significantly lower than controls, but the pattern of their circadian rhythms was maintained (30).…”
Section: Discussionmentioning
confidence: 89%
“…Circadian variation of bone remodelling is shown by levels of markers of bone resorption (urinary excretion of urinary cross-linked N-telopeptide of type 1 collagen (NTx) (40) and pyridinium cross-links (41,42)) and formation (serum osteocalcin, respectively (43, 44)): peak levels occur at night with a nadir in the afternoon. The levels of osteocalcin fall following the rise in serum cortisol, with a latency w4 h (45).…”
Section: Defects In Bone Metabolismmentioning
confidence: 99%
“…Bone turnover in laboratory animals and humans reportedly undergoes a circadian rhythm, with bone resorption and, to a lesser extent, bone formation increasing at night [1][2][3]. Such rhythms have clinical implications for the timing of sample collection and for the assessment of a given therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%